2019
DOI: 10.1071/wr19074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free-ranging dogs and cats on medium-sized wild mammal assemblages in urban protected areas of a Mexican city

Abstract: ContextUrban protected areas (PAs) are the habitat of several Neotropical medium-sized wild mammal (MSWM) species. However, this richness is seriously threatened by the growing populations of free-ranging dogs and cats in these areas. AimsThe aim of the present study was to evaluate the effect of free-ranging dogs and cats on the assemblage structure of MSWM in PAs of Xalapa city, Veracruz, Mexico. MethodsCamera traps were used to assess the effect of abundance and activity of dogs and cats on richness, abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Like reports in Brazil and Mexico, where dogs consume medium sized mammals including other carnivores (Campos et al, 2007;Mella-Méndez et al, 2019), we found gray fox and bobcat in the scats of free-ranging dogs. Whether these species were killed or scavenged by dogs is unknown.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Like reports in Brazil and Mexico, where dogs consume medium sized mammals including other carnivores (Campos et al, 2007;Mella-Méndez et al, 2019), we found gray fox and bobcat in the scats of free-ranging dogs. Whether these species were killed or scavenged by dogs is unknown.…”
Section: Discussionsupporting
confidence: 85%
“…Whether these species were killed or scavenged by dogs is unknown. Skunks are considered to be medium sized mammals and thus, could be a threatened prey of free-ranging dogs (Gallina et al, 2008;Mella-Méndez et al, 2019).We present the first evidence of the consumption of hooded skunk (Mephitis macroura), and eastern hognosed skunk (Conepatus leuconotus) by free-ranging dogs, which also were the most frequent species found. Freeranging dogs in CEP may be assuming the role of wild canids, acting as both predators and competitors with other mammals (Vanak & Gompper, 2009a.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Beyond their presence, growing research shows how these species have a negative impact on native wildlife, thereby converting themselves into conflictive invasive species [103,104]. In the case of cities, the presence of cats and dogs (domestic or feral) may increase spatial-use conflicts with wildlife in urban green areas [105,106], also affecting native mammal, bird, reptile and amphibian communities by predation [107]. Finally, the high densities of these species can threaten public health by increasing the prevalence of diseases such as toxoplasma and rabies [108,109].…”
Section: Conservation Implicationsmentioning
confidence: 99%